The first observations of auroras with dynamic vision sensors - Andreas Stokholm; Njål Gulbrandsen; Nicolas Pedersen; Andrzej Kucik; Daniel Haugård Olesen; Anna Naemi Willer; Olivier Chanrion; Sine Munk Hvidegaard (Scientific Reports)
Abstract Auroras are space weather light phenomena caused by interactions between the solar wind, Earth’s magnetic field, and Earth’s atmosphere. Scientific aurora images are often captured with camera exposure times of up to 1-2 seconds for sufficient light input. However, long exposure times also intensify other light emissions, e.g. urban- and moonlight, thus, dark night conditions are preferred. Studies have carried out high-speed imaging with up to 160 Hz, but higher has been elusive. Here, we propose to use the emerging Dynamic Vision Sensors (DVS) technology as an alternative or complementary imaging approach for auroras with high dynamic range (110–120 dB) and sampling rate (5KHz–1MHz). We present the first observations of auroras at 5KHz using DVS, highlighting the potential use within this application. Approaches to reconstructing the brightness intensity image are introduced, giving the photon flux for each pixel and the whole sensor, mimicking a photometer. We show that DVS can observe auroras in challenging urban- and moonlight conditions in high-temporal resolution, enabling a paradigm shift within the scientific field. Finally, we discuss the use of DVS more broadly within geoscience.